2022
DOI: 10.1002/hpja.603
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a trial of an age‐friendly dining initiative: Dining Co

Abstract: Objectives With the rise of age‐friendly cities and communities, increasing attention is being paid to coproducing age‐friendly guidelines with older people and community stakeholders. Little is known however about age‐friendly guidelines for dining establishments. Methods A three‐stage study to develop general and contextualised requirements for an age‐friendly dining experience was conducted in the City of Onkaparinga, South Australia. The first stage involved older people in co‐designing aspects of an age‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A preliminary search of PROSPERO, MEDLINE (Ovid), the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis identified some systematic reviews and scoping reviews pertaining to co-design and older people that were published or are in-progress 20,21 ; these were mostly performed within community settings rather than in residential aged care settings 22,23 . The research team’s knowledge of published literature on co-design in residential aged care,(eg 24–26 ) indicates that the current search would yield relevant results.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary search of PROSPERO, MEDLINE (Ovid), the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis identified some systematic reviews and scoping reviews pertaining to co-design and older people that were published or are in-progress 20,21 ; these were mostly performed within community settings rather than in residential aged care settings 22,23 . The research team’s knowledge of published literature on co-design in residential aged care,(eg 24–26 ) indicates that the current search would yield relevant results.…”
Section: Introductionmentioning
confidence: 99%